Long-Term Postpartum Outcomes of Insulin Resistance and β-cell Function in Women with Previous Gestational Diabetes Mellitus - Zhirong Miao; Honghua Wu; Liu Ren; Nan Bu; Lili Jiang; Huixia Yang; Junqing Zhang; Xiaohui Guo (International Journal of Endocrinology)
Aims. The objective of the present study was to explore the long-term postpartum glucose metabolism in women with previous GDM, and study the mechanism of hyperglycemia from gestation to postpartum by investigating the postpartum insulin resistance and insulin secretion. Methods. A total of 321 females with previous GDM were followed up once during 1- to 6-years postpartum. Characteristics during pregnancy, perinatal period, and postpartum were compared between postpartum NGT and hyperglycemic women. HOMA-IR and HOMA-β were used to assess insulin resistance and insulin secretion levels with different glucose statuses. Results. The prevalence of postpartum hyperglycemia had a fluctuant increase from 25.9% at 1 year, to 53.7% at 5 year. 75 g OGTT 2 hPG during pregnancy was an independent predictor of postpartum hyperglycemia with an OR of 2.15 (95% CI 1.245, 3.722) (P=0.006). After ROC analysis, the best equilibrium between sensitivity (70.3%) and specificity (60.4%) for 2 hPG was 9.03 mmol/L. HOMA-IR was increased in postpartum normal glucose tolerance (NGT), prediabetes, and T2DM (1.64 vs. 2.14 vs. 4.27, P<0.001), while HOMA-β was decreased (1.19 vs. 1.11 vs. 0.71, P=0.011). In pairwise comparison, except for HOMA-IR between prediabetes and T2DM, and HOMA-β between NGT and prediabetes, other differences showed significance. Conclusions. 75 g OGTT 2h PG during pregnancy higher than 9.03 mmol/L is regarded as an independent risk factor of postpartum hyperglycemia. Insulin resistance with insufficient insulin secretion compensation is still common phenomenon during long-term postpartum. Women with heavier insulin resistance in the postpartum period are more likely develop prediabetes, while decreased β-cell function contributes more to T2DM development.